Analisis Kemampuan Menulis Siswa Kelas III SDK Wano Badu dalam Menulis Kalimat Sederhana - Rato, Marthen Ana; Lende, Petrus; Mila, Daindo; Bili, Kristoforus Dowa (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyse the writing skills of Year 3 pupils at SDK Wanno Badu in constructing simple sentences. The study employed a descriptive qualitative approach with a sample of 20 pupils. Data collection was carried out through interviews, writing tests, and documentation of the pupils’ written work. The results of the study indicate that 11 pupils, or 55%, have demonstrated a reasonably good ability to write simple sentences, particularly in the use of the basic subject–predicate structure. However, 9 pupils, or 45%, still face several challenges, including inconsistent use of capital letters, punctuation errors, and ineffective sentence structure. These findings suggest that the pupils’ writing skills have not yet developed optimally and still require targeted guidance. Overall, this study emphasises the need to improve the writing skills of Year 3 pupils at SDK Wanno Badu through continuous writing practice, teaching tailored to pupils’ potential and intelligence as outlined in Gardner’s theory of multiple intelligences, and the provision of immediate and consistent feedback by teachers during the writing learning process.